Population pharmacokinetics and exposure–response analyses of safety (ARIA‐E and isolated ARIA‐H) of lecanemab in subjects with early Alzheimer's disease - Oneeb Majid; Youfang Cao; Brian A. Willis; Seiichi Hayato; Osamu Takenaka; Bojan Lalovic; Sree Harsha Sreerama Reddy; Natasha Penner; Larisa Reyderman; Sanae Yasuda; Ziad Hussein (CPT: Pharmacometrics & Systems Pharmacology)
Abstract Lecanemab (Leqembi®) was recently approved by health authorities in the United States, Japan, and China to treat early Alzheimer's disease (AD), including patients with mild cognitive impairment (MCI) or mild dementia due to Alzheimer's disease upon confirmation of amyloid beta pathology. Extensively and sparsely sampled PK profiles from 1619 AD subjects and 21,929 serum lecanemab observations from two phase I, one phase II, and one phase III studies were well characterized using a two‐compartment model with first‐order elimination. The final PK model quantified covariate effects of body weight and sex on clearance and central volume of distribution, ADA‐positive status, and albumin on clearance, and of Japanese ethnicity on central and peripheral volumes of distribution. Exposure to lecanemab was comparable between two lecanemab‐manufacturing processes. However, none of the identified covariates in the model had a clinically relevant impact on model‐predicted lecanemab Cmax or AUC at steady state following 10 mg/kg bi‐weekly. Importantly, age, a well‐recognized risk factor for AD, was not found to significantly affect lecanemab PK. The incidence of ARIA‐E as a function of lecanemab exposure was modeled using a logit function with data pooled from 2641 subjects from the phase II and phase III studies, in which a total of 177 incidences of ARIA‐E were observed. The probability of ARIA‐E was significantly correlated with model‐predicted Cmax and predicted to be higher in subjects homozygous for APOE4. The incidence of isolated ARIA‐H was not associated with lecanemab exposure and was similar between placebo and lecanemab‐treated subjects.